CONTINUITY IDEMPOTENT PROTUBERANT COMBINATION OF ENDLESS AMOUNT OF ELEMENTS I-OPOUCLOGO COMPACT - Глушак, Інна Дмитрівна; Никифорчин, Олег Ростиславович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Idempotent protuberant combination of endless amount of elements of I-convexity compact is built and it is led to, that she continuously depends on the arguments, if last to understand as the reserved great number in topology work of compact on a single segment-hyperspace element with a topology Vietoris.